Evaluation of Malinau State Vocational Secondary School (SMK) Library Organization - Yuris Rina Saranga; Meilina Bustari (Jurnal Penelitian Pendidikan IPA, 2025)
This study evaluates the management of school libraries in three vocational schools in Malinau—SMK Negeri 1, SMK Negeri 2, and SMK-SPP Negeri Malinau—based on the National Standards for Libraries in Senior High and Vocational Schools (Peraturan Kepala Perpustakaan No. 12 Tahun 2017). Using an evaluation research design, data were collected through observations, interviews, and documentation involving school principals, library heads, teachers, and students. The findings indicate several challenges, including insufficient technology, outdated resources, limited space, and inadequate staff support, which hinder library effectiveness. To address these issues, improvements in technological infrastructure, space optimization, resource enhancement, and staff development are necessary. Strengthening school library management is expected to improve the learning environment, academic achievement, and information literacy among students. These findings provide valuable insights for school administrators and policymakers to align library management with national standards and enhance their role in supporting education.